Analyzing Bio-Geo-Chemical Factors in Relation to Land Use Trends on Basalt Terrain in Dong Nai and Nearby Areas - Bac, Dang Kinh; Bao, Dang Van (VNU Journal of Science: Earth and Environmental Sciences, 2020)
Basalt terrain is widely distributed in the Central Highlands and Southeast of Vietnam. Currently, land use policies on basalt types are not really suitable, affecting economic growth and creating negative impacts on the environment, especially soil and water pollution. This study carried out the assessment of bio-geochemical conditions in three types of basalt terrain, using 16 remote sensing indices. The relationship between these indices is analyzed based on correlation matrix and structural equation model (SEM). The results show different land use management trends across the three basalt types. The results encourage the land-use management to (i) expand and maintain the protected forests on Miocene basalt; (ii) develop agriculture on the Pliocene - Pleistocene basalt terrain; and (iii) improve soil quality and ecotourism on late Pleistocene basalt terrain.